Analysis of Governmental Role in the Chinese Stock - Jin, ShanShan (2007)
By analyzing the unique political-economic context in which the Chinese stock market was established, this paper presents an analysis of the governmental role throughout the history of the Chinese stock market. It shows that the Chinese government is intimately involved in establishing and promoting the stock market in China, and up to now it still keeps some formal and informal connections with the listed companies and the regulatory framework. Motivated by recent success of incorporating game-theoretic approach into macro-economic issues, this paper models the strategic interactions between the government and the investors in the Chinese stock market as a signalling game with asymmetric information. Two sets of signalling mechanisms are proposed: separating equilibrium and pooling equilibrium. An empirical study is carried out by associating the Shanghai Stock Exchange Composite with political news from 1991 to 2002. A signalling mechanism, which is similar to separating equilibrium, is found. Moreover, signal failures, which are caused by the conflicting governmental considerations in the stock market and the relative inexperience of the investors in the Chinese stock market, are revealed in this empirical study as well. Based on these two important findings, we recommend that the Chinese government should change its attitudes towards stock market, and the regulatory system should establish itself as a neutral market referee.